Mechanical Characterization of Sumbawa Local Sisal Fiber Polyester Composite Sandwich Panel compared to Meranti Wood Panels - Fitrayudha, Adryan; Hidayati, Nurul; Zarkasi, Ahmad (Universitas Tribhuwana Tunggadewi Malang, 2023)
The development of composite material engineering is an effective solution for the development of green building-based materials that are being campaigned in various parts of the country today. The fundamental problem in composite engineering that is developing is the lack of use of environmentally friendly materials as the basic material for composite constituents. The use of natural fiber-based composite materials as reinforcement is one of the right solutions to answer the issue of green building in producing more environmentally friendly materials with much better mechanical resistance. The study aims to determine the flexural characteristics of sandwich panel beams of sengon (SPS) in comparison to Meranti beams. The material used as skin for SPS beams is a composite of sisal fiber polyester from Sumbawa Island. Test standard based on ASTM C393 (length 550 mm, width 50 mm, thickness 25 mm), with a total of 5 specimens each. The test results showed that the SPS beams had an average bending stress of 167.66 MPa, while the Meranti wood beams produced an average bending stress of 94.29 MPa. The amount of bending stress produced by SPS beams is 43.38% higher than meranti wood beams. The average deflection value of SPS beams is 20.34 mm, greater than the average deflection value of sengon wood of 15.42 mm. This shows that the use of sisal polyester composite skin on SPS beams can produce better mechanical characteristics compared to Meranti wood.ABSTRAKPerkembangan rekayasa material komposit merupakan solusi yang efektif bagi pengembangan material berbasis green building yang sedang dikampanyekan di berbagai belahan negara saat ini. Permasalahan mendasar dalam rekayasa komposit yang tengah berkembang adalah minimnya penggunaan material ramah lingkungan sebagai bahan dasar penyusun komposit. Penggunaan material komposit berbasis serat alam sebagai perkuatan (reinforcement) merupakan salah satu solusi yang tepat guna menjawab isu green building dalam menghasilkan material yang lebih ramah lingkungan dengan ketahanan mekanis yang jauh lebih baik pula. Penelitian ini bertujuan untuk mengetahui karakteristik lentur pada balok sandwich panel kayu sengon (SPS) dengan pembanding balok kayu meranti (kayu kelas II). Material yang digunakan sebagai skin pada balok SPS adalah komposit polyester serat sisal yang dibudidayakan di Pulau Sumbawa, Nusa Tenggara Barat. Standar pengujian berdasarkan ASTM C393 (panjang 550 mm, lebar 50 mm, tebal 25 mm), dengan jumlah masing-masing 5 benda uji. Hasil pengujian menunjukkan balok SPS memiliki tegangan lentur rata-rata sebesar 167,660 MPa, sedangkan pada balok kayu meranti menghasilkan tegangan lentur rata-rata sebesar 94,292 MPa. Besarnya tegangan lentur yang dihasilkan balok SPS lebih tinggi 43,380% dibandingkan balok kayu meranti (kayu kelas II). Nilai lendutan rata-rata pada balok SPS sebesar 20,340 mm, lebih besar dibandingkan nilai lendtan rata-rata kayu sengon sebesar 15,420 mm. Hal tersbut menunjukkan bahwa penggunaan skin komposit polyester sisal Sumbawa pada sandwich panel kayu sengon mampu menghasilkan karakteristik mekanik yang lebih baik dibandingkan dengan kayu Meranti.